Clinical application of foot strike run retraining for military service members with chronic knee pain. Issue 4 (25th May 2021) - Mazzone, Brittney; Yoder, A; Condon, R; Farrokhi, S
Abstract : Introduction: Military training is associated with a high incidence of knee pain. Conversion from a rearfoot to non-rearfoot strike during running is effective at reducing knee pain in research environments. The purpose of this report was to demonstrate run retraining as a clinical intervention for service members with knee pain. Methods: Sixteen service members with running-related chronic knee pain underwent run retraining that converted foot strike from a rearfoot to a non-rearfoot strike using real-time visual feedback. The Lower Extremity Functional Scale (LEFS) and Numerical Pain Rating Scale (NPRS) for knee pain during running were assessed pretraining, at the final training session and at a 1-month follow-up. During running, foot inclination angle and vertical ground reaction force (VGRF) average loading rate were measured pretraining and at 1 month of follow-up. Results: Service members underwent 7.4±1.0 training sessions over the course of 15.8±4.6 days. LEFS improved by 8±6 points immediately after retraining, with an overall improvement of 10±6 points from pretraining to 1-month follow-up (p<0.01). NPRS improved by 2.0±0.4 points immediately after retraining, with an overall improvement of 2.0±0.4 points from pretraining to 1-month follow-up (p<0.01). Conversion to a non-rearfoot strike pattern was apparent at follow-up for all but two patients. VGRF average loading rate decreased by 56%±17% (p<0.01) from pretraining to 1-month follow-up. Conclusions: Knee pain and function improved as a result of non-rearfoot strike run retraining, which supports the clinical use of this evidence-based intervention.